Air menjadi anggur dalam perkawinan di Kana: Sebuah tanda penyataan diri Yesus sebagai Anak Allah - James Anderson Lola; Darius Darius (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
This is a qualitative research article with an exegesis approach to finding the meaning of the miracle of the water turning into wine in the marriage at Cana which is recorded in John 2:1-11. The miracle of water turning into wine in the perspective of the Gospel of John is the first miracle that Jesus did to reveal Himself as the Son of God which fulfilled God's Covenant in the Old Testament. The miracle of water turning into wine is a miracle that must be understood in the theological perspective and the agenda of the Gospel of John which is intended to display the presence of Jesus and all that He did in history as an expression of Jesus' identity as the Son of God as well as the fulfillment of God's promise in the Old Testament.AbstrakPenelitian ini adalah penelitian kualitatif dengan pendekatan eksegesis untuk menemukan makna dari peristiwa mujizat air berubah menjadi anggur dalam perkawinan di Kana yang dicatat dalam Yohanes 2:1-11. Mujizat air berubah menjadi anggur dalam perspektif Injil Yohanes merupakan mujizat pertama yang Yesus lakukan untuk memberikan penyataan diri-Nya sebagai Anak Allah yang menggenapi Perjanjian Allah di dalam Perjanjian Lama. Mujizat air berubah jadi anggur adalah mujizat yang harus dipahami dalam perspektif teologis dan agenda dari Injil Yohanes yang memang bertujuan untuk menampilkan kehadiran Yesus dan semua yang Ia lakukan dalam sejarah sebagai penyingkapan identitas Yesus sebagai Anak Allah sekaligus juga adalah pemenuhan dari janji Allah di dalam Perjanjian Lama